Fluorescent Guided Surgery in the Surgical Management of Glioma: The Dawn of a New Era - Kostas N. Fountas (Brain Sciences, 2020)
A growing body of evidence supports the importance of marginal or even supramarginal resection in cases of high- but also of low-grade gliomas [...]